2008
DOI: 10.1186/1758-2652-11-s1-p45
|View full text |Cite
|
Sign up to set email alerts
|

Excellent short-term CD4 recovery with a PI- and NRTI-sparing regimen in triple-class failure HIV-infected patients: raltegravir, maraviroc, etravirine

Abstract: Purpose of the studyWith the availability of new drug classes, the full suppression is a realistic goal even for heavily pre-treated patients. We prospectively evaluated the magnitude of CD4 recovery (CR) in this setting. MethodsWe decided to simultaneously screen triple class failing patients (pts) followed at San Raffaele Hospital in three Expanded Access Programs: raltegravir (MK0518-023), maraviroc (A4001050), etravirine (TMC125-C214). Salvage therapy was prescribed according to: viral tropism, screening g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Overall, it appears that reductions in maraviroc exposure observed due to co‐administration with raltegravir are unlikely to affect the antiretroviral activity of maraviroc. Notably, in a combination study with raltegravir, maraviroc and etravirine in heavily pretreated HIV‐infected patients harbouring R5 co‐receptor‐using virus, 90% of patients had undetectable viral load (<50 copies ml −1 ) at week 48 [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, it appears that reductions in maraviroc exposure observed due to co‐administration with raltegravir are unlikely to affect the antiretroviral activity of maraviroc. Notably, in a combination study with raltegravir, maraviroc and etravirine in heavily pretreated HIV‐infected patients harbouring R5 co‐receptor‐using virus, 90% of patients had undetectable viral load (<50 copies ml −1 ) at week 48 [15].…”
Section: Discussionmentioning
confidence: 99%
“…Raltegravir trough plasma concentration (ng ml -1 ) on day 3 (raltegravir) and day 14 maraviroc + raltegravir) patients harbouring R5 co-receptor-using virus, 90% of patients had undetectable viral load (<50 copies ml -1 ) at week 48 [15].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A number of nonrandomized studies have reported on the virological and immunological efficacy of raltegravir for treatment-experienced subjects (46)(47)(48)(49), including in combination with etravirine and darunavir (50-52). These primarily clinic-based studies further confirm the benefits observed in randomized clinical trials of raltegravir as a component of combination therapy for treatment experienced patients.…”
Section: Raltegravir Efficacy Treatment-experienced Hiv-infected Adultsmentioning
confidence: 99%
“…5-7 These 3 agents have been used in combination with other active ARV medications to create potent, fully suppressive regimens. 8 However, in some patient populations, the only remaining fully active ARV medications are these 3 agents. This case-series reviews patients from a large HIV patient cohort that were treated with these 3 agents in combination and reports on the tolerability and effectiveness of this regimen.…”
mentioning
confidence: 99%